Aktivasi Akhlak Uswatun Hasanah Nabi Menjawab Patologi–Moral-Sosial Di Indonesia - Zaitur Rahem (Jurnal Dakwah dan Komunikasi, 2017)
Public confidence in the figures in this negei continues to shrink. People began to turn to a number of figures which are initially considered competent-charismatic. The reason, because practices that are very human behavior. Some unscrupulous public figure to do one action out of the bounds of morality and culture there. Studies in this paper tries to pick a phenomenological facts universally immoral behavior. Through qualitative methods, and data collection techniques snawball sampling, data sources can be tracked easily. Hasilya, portrait decrease civilized behavior is caused by a sense of optimism and spirit tegerusnya elements of the nation (especially Muslims) in addressing the noble values taught by the Prophet in the texts of Islam (Quran and Hadith)